Chronic Non-infectious Osteomyelitis Mimicking Scurvy as the Presenting Sign of Crohn’s Disease: Case Report - Goldfarb, Alexa; Breitling, Stefan; Amadasun, Owen; Kiernan, Bridget; Gold-von Simson, Gabrielle; Sagalowsky, Selin T. (Frontiers in Pediatrics, 2022)
Chronic non-infectious osteomyelitis (CNO) is a rare, inflammatory process associated with pediatric inflammatory bowel disease (IBD). Signs and symptoms of CNO parallel scurvy, a nutritional deficiency that can affect children with autism spectrum disorder (ASD). This is the first report of a child initially thought to have scurvy, then subsequently diagnosed with CNO as the presenting manifestation of Crohn’s disease. This case enhances the literature elucidating extra-intestinal manifestations of IBD and pediatric nutritional deficiencies.